Daoist Creativity through Interconnectedness and Relational Dynamics in Pedagogy - Wang, Hongyu (Philosophical Inquiry in Education, 2022)
Reconceptualizing the notion of creativity is imperative for addressing today’s multilayered social, ecological, and educational crises. This paper draws upon the Daoist philosophy of creativity, which connects rather than separates, to elaborate on the creative relational dynamics of a Daoist pedagogy. First, Western conceptions of creativity are briefly discussed to situate Daoist creativity relative to other scholarship. This discussion is followed by exploring three important aspects of Daoist creativity through interconnectedness: the self-creative process of the cosmos, the co-creativity of human creativity in spontaneity, and the virtuous pursuit of creative harmony. Conceptualizing Daoist creativity in these three aspects lays the foundation for the formulations of contemporary Daoist pedagogical dynamics. First, relational ontology underlies non-dualistic knowing and creative learning, which is infused with meditative sensitivity and incorporates aesthetic modes of thinking and associative thinking across boundaries. Second, creative personhood through integrating opposites and becoming attuned to the creative energy of life requires the personal cultivation of both the instructor and students while transforming teacher–student relationships. Third, a Daoist pedagogy of harmonizing creative tensions is envisioned through making connections across difference, diversifying texts, enacting pedagogical attunement, and harmonizing different modes of knowing and being.